Thyroid Dysfunction and Psoriasis: A Possible Association Revisited - Borges, A. S.; Brasileiro, A. (Journal of the Portuguese Society of Dermatology and Venereology, 2018)
Psoriasis is a chronic, common skin disease, which affects the patient’s quality of life to the highest degree. Several exogenous and endogenous factors may act as triggers for psoriasis, as certain hormonal changes. Previous studies have shown that thyroid hormones may be implicated in the physiopathology of psoriasis. This paper reviews the role of thyroid hormones in psoriasis as well as the current scientific evidence of a possible association between psoriasis and thyroid dysfunction.